Paliperidone for the Treatment of Ketamine-Induced Psychosis: A Case Report. (August 2014) - Zuccoli, M. L.; Muscella, A.; Fucile, C.; Carrozzino, R.; Mattioli, F.; Martelli, A.; Orengo, S.
Ketamine is an anaesthetic and analgesic drug synthesized in the 1960s from phencyclidine. The recreational use of ketamine increased among the dance culture of techno and house music, in particular in clubs, discotheques, and rave parties. The psychotropic effects of ketamine are now well known and they range from dissociation to positive, negative, and cognitive schizophrenia-like symptoms. We report a case of a chronic oral consumption of ketamine which induced agitation, behavioral abnormalities, and loss of contact with reality in a poly-drug abuser; these symptoms persisted more than two weeks after the drug consumption had stopped. Antipsychotic treatment with paliperidone led to a successful management of the psychosis, getting a complete resolution of the clinical picture. Paliperidone has proven to be very effective in the treatment of ketamine-induced disorders. Moreover, the pharmacological action and metabolism of paliperidone are poorly dependent from the activity of liver enzymes, so that it seems to be one of the best second generation antipsychotics for the treatment of smokers and alcohol abusers.